Implementasi Senam B-Fit Bagi Pekerja Rumah Sakit Di Kota Malang - Erianto Fanani; Tisnalia Merdya Andyastanti; Hilma Tsurayya Iftitahurroza; Fida Rahmayanti; Nauval Akhmadian Gelaner; Zaidhan Lucano Fulviansyah; Farhan Rahadi Wibowo; Ajeng Sri Suhartanti (Poltekkes Kemenkes Malang, 2025)
Musculoskeletal disorders (MSDs) are one of the main factors causing reduced productivity of workers, especially medical personnel. Hospital employees, have a high risk of experiencing health problems, especially in the muscles and joints as a result of their static work positions and postures that last for a long time. A prevention effort is needed so that hospital employees can avoid muscle and joint problems that can affect their productivity. This can be prevented by the application of B-Fit exercises between the work activities of medical personnel. Based on the Ministry of Health's recommendation, the B-Fit exercise is done in 4 movements with a duration of no more than 3 minutes. The main targets of B-fit exercise are Brimedika General Hospital’s personnel who spend most of their time sitting while facing patients. This activity was attended by 28 participants consisting of doctors, nurses, administrative staff, cleaning service RSU Brimedika. The results showed that the implementation of B-fit exercises was felt to increase flexibility, muscle strength, and reduce the risk of injury due to poor posture. In addition, B-fit exercises can also improve mood, reduce stress, and increase work productivity. B-fit exercise is an effective and efficient intervention to improve the health and well-being of medical personnel at Brimedika General Hospital. It is recommended to make a sustainable program in the form of implementing the B-Fit exercise routine according to the Ministry of Health's recommendations which is 2 times B-Fit in a day.